Kondisi Eksisting dan Kenormalan Baru Usaha Mikro dan Kecil Olahan Ikan Kabupaten Demak Hadapi Pandemi - Berta Bekti Retnawati; Ch Retnaningsih (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Surakarta, 2021)
current situation is much harsher than previous economic crises. This crisis situation continues to make MSMEs a safety valve for the nation's economy because of the very large number of business actors and the absorption of labor in them. Much hope is given to the food sector, which has always been a priority and primary choice compared to other secondary needs. Research was carried out to see the existing conditions and adaptive and survival efforts of this marine-based micro and small food processing center in three times conditions: before a pandemic, during a pandemic, and efforts in a new normal. Prior to the pandemic, business actors marketed products in the Demak area and several cities outside Demak, and almost half of the respondents had a large amount of production per month (above 1000 kg). In the marketing process of processed seafood products, business actors had not yet utilized technology information such as social media to market their products. During the Covid-19 pandemic, the business situation for processed seafood products continued as usual even though there were 3% of respondents who temporarily closed their businesses. The impact of the decline in income can still be felt even though business operations can still be carried out in the same areas as before the pandemic. The findings in the field that most of the respondents did not adapt to their business and continued to run their business as before the crisis. Entering the new normal, almost all respondents plan to continue their business. In this plan, respondents do not have a specific target for their business. But on the other hand, respondents hope to receive assistance with both capital and training needed to deal with difficult situations that will still occur in the new normal. The synergy of various parties is needed to strengthen them in business continuity